A study of SnO2 nanowire FET devices: ambipolarity effect induced by UV Light exposure and their use as UV sensors - Arantes, Adryelle do Nascimento (Universidade Federal de São Carlos, 2021)
In this work, SnO2 nanowires (NW) were grown by the Vapor-Liquid-Solid (VLS) method and used to build single NW FET devices. As-grown samples went through structural and morphological analysis and seven single NW devices were built, with a back-gated FET architecture, by direct photolithography. SnO2 NWs grown by VLS method presented the desired tetragonal structure and monocrystalline character, inspected by XRD and HRTEM techniques. In addition, the as-grown samples morphology of a NW with lengths of tens of micrometers and cross-section mostly displaying rectangular geometry were assured through SEM images. The device fabrication process by direct photolithography was proven to be efficient to build the back-gated FET architecture devices with great electrical contacts quality. Single SnO2NWFET’s transport properties were explored, where on/off ratio, mobility and carrier density parameters were extracted, resulting in values around 105, lower than 0.1 cm2/V and in the order of 1019/cm3, respectively. Schottky barrier heights were estimated, considering the gate bias as grounded and room temperature, and Φ_Bn values between 0.41 and 0.75 eV were found. Afterwards, different conditions were analyzed: the device (1) under positive gate bias (V_G>0) and no applied source/drain bias (V_DS=0); (2) V_DS>0 and V_G>0; (3) V_DS<0 and V_G<0 and (4) V_DS<0 , V_G<0 but under UV illumination. Regarding the latter, all devices presented UV induced ambipolary effect, where on/off states ratio with values of the same order were obtained and ranged from 1.1 to about 19.3. A simple band model to explain the observed behavior, i.e., describe how both types of carriers can contribute to the final current depending on the biasing was proposed. Ambipolarity is one of those effects that may direct its use for specific purposes, where a controllable separated unipolar mode can be achieved in one single device. Furthermore, the devices were tested as UV sensors and presented satisfactory results: as a UV photodetector, the acquired I_on⁄I_off ratio was found to be of the order of 〖10〗^4 for all devices investigated. In addition, rise time was found to range 0.56 s < τ_r< 0.63 s, whereas the decay time 0.54 s < τ_d< 0.75 s. According to those results, one can assure their huge feasibility as a UV sensor.
Um estudo de dispositivos de nanofios de SnO2: efeito de ambipolaridade induzido por luz UV e o uso como sensores de luz UV
Keywords: FET de um único nanofio de SnO2; Nanofios de SnO2; Ambipolaridade induzida; Fotodetector de luz UV.; SnO2 single nanowire FET; SnO2 nanowires; VLS growth; Induced ambipolarity; UV photodetector.; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::TRANSP.ELETRONICOS E PROP. ELETRICAS DE SUPERFICIES;INTERFACES E PELICULAS